Shading responses are species-specific in thermally stressed corals - Ellis, Sophia L.; Butcherine, Peter; Tagliafico, Alejandro; Hendrickson, Conor; Kelaher, Brendan P.; Schulz, Kai G.; Harrison, Daniel P. (Frontiers in Marine Science, 2024)
Light is critical to coral growth through endosymbiont photosynthesis but can also act with elevated temperatures to cause coral bleaching. When more light is absorbed than can be used for photosynthesis, elevated irradiance can damage symbiont photosynthetic machinery. Hence, solar-radiation management through shading has been suggested to alleviate coral bleaching during marine heatwaves. Acropora divaricata and Acropora kenti were tested at two temperatures with 30% shading and an unshaded control to determine the relative impacts of light and temperature on coral bleaching severity. The coral bleaching response was assessed by photochemical (pulse amplitude modulated fluorometry), physiological (symbiont density, chlorophyll a concentration, catalase activity, and lipid peroxidation), and physical (mean intensity of grey or ‘percentage whiteness’) markers. Shading significantly reduced the bleaching response in A. divaricata, whilst for some parameters A. kenti responded negatively to shade. In A. divaricata, shading prevented photochemical collapse up to the experiment’s maximum 4.4 degree-heating weeks (DHW). Biomarkers of coral bleaching stress responded to shade and water temperature at 4.4 DHW; catalase activity was greatest in the shaded and ambient temperature treatment. Shading did not reduce the effects of bleaching in A. kenti; the mean intensity of grey and light saturation coefficient was greatest in the shaded treatment. Shading did, however, reduce lipid peroxidation at 3 DHW. Our results suggest shading during thermal stress may only protect some coral species, highlighting the need to consider species-specific responses when evaluating the potential efficacy of coral bleaching interventions.